2014
DOI: 10.3390/nano4010046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Frequency AC Magnetic Susceptibility and Magnetic Properties of CoFeB/MgO/CoFeB Magnetic Tunnel Junctions

Abstract: In this investigation, the low-frequency alternate-current (AC) magnetic susceptibility (χac) and hysteresis loop of various MgO thickness in CoFeB/MgO/CoFeB magnetic tunneling junction (MTJ) determined coercivity (Hc) and magnetization (Ms) and correlated that with χac maxima. The multilayer films were sputtered onto glass substrates and the thickness of intermediate barrier MgO layer was varied from 6 to 15 Å. An experiment was also performed to examine the variation of the highest χac and maximum phase angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Different parts of the M(H) curve can be studied by applying a vari-able DC magnetic field (H) oriented parallel (antiparallel) to H AC . A number of new possibilities of this method adopted for the investigation of various materials including superconductors [24,25] have been demonstrated earlier [26][27][28].…”
Section: Methodsmentioning
confidence: 99%
“…Different parts of the M(H) curve can be studied by applying a vari-able DC magnetic field (H) oriented parallel (antiparallel) to H AC . A number of new possibilities of this method adopted for the investigation of various materials including superconductors [24,25] have been demonstrated earlier [26][27][28].…”
Section: Methodsmentioning
confidence: 99%
“…Weakening of the transmitted electromagnetic radiation opens up a wide range of perspectives for microwave absorbers [ 14 , 15 , 16 , 17 ]. Hard and soft ferrites are technologically important materials owing to their special applications in data-storage media, microwave devices [ 18 ] and permanent magnets [ 19 ]. Because strong exchange-coupling occurs [ 20 ] between two soft and hard magnetic phases, an intensification of the microwave absorption can be observed [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 3 , 4 ] have published two papers on the properties of CoFeB/MgO/CoFeB and CoFeB/AlOx/Co Magnetic Tunnel Junctions (MTJs). In one paper, the MgO barrier layer thickness in CoFeB/MgO/CoFeB MTJs was varied to measure low-frequency alternate-current magnetic susceptibility and magnetic properties.…”
mentioning
confidence: 99%
“…It was suggested that the spin sensitivity is related to both highest magnetic susceptibility and maximum phase angle. Moreover in this work it was demonstrated that the indirect spin exchange coupling of top CoFeB and bottom CoFeB layers in CoFeB/MgO/CoFeB oscillates [ 3 ]. Similarly, in the other paper, the CoFeB/AlO x /Co multilayer film was used to investigate the strength of indirect spin exchange-coupling between CoFeB and Co strength and the χ ac in a low-frequency alternating magnetic field, for various thicknesses of the barrier layer AlO x [ 4 ].…”
mentioning
confidence: 99%